Kontribusi Pendapatan Hasil Tangkap Ikan Laut terhadap Pendapatan Rumah Tangga Nelayan di Desa Bogak, Kecamatan Tanjung Tiram, Kabupaten Batubara (Jurnal Agribisnis dan Agrowisata, 2025)
Contribution of Marine Fish Revenue to Fisherman Household Income in Bogak Village, Tanjung Tiram District, Batubara Regency. Batubara Regency is one of the regencies in North Sumatra Province which has potential in the fisheries sector and the people who live in this area generally work as fishermen, in addition to agriculture and other businesses. The purpose of this study was to examine the amount of income from fishing from sea fishing and to analyze the contribution of income from fishing from sea fishing to fishermen's household income in Bogak Village, located in Tanjung Tiram District, Batubara Regency. The number of research samples taken were 34 fishermen. Data analysis was carried out by using the income formula for fishing fishermen and analyzing the contribution of fishermen's catch to fishermen's household income by measuring the percentage (%). The results of this study show that fishermen's income in September 2022 is IDR985.230. The contribution of marine fish catches is included in the moderate category, namely 43,67%. Suggestions that need to be considered are that it is better for fishermen to follow technological developments used in the development of fishing businesses in order to produce more production. The government is expected to be more supportive of fishermen, provide encouragement and appropriate counseling so that fish production produced by fishermen can be increased.
Keywords: contribution; fisherman; income; sea fish